The Sociological Approach to the Values of the Manager - E. S. Gurenko; E. H. Karpova (Дискурс, 2022)
Introduction. This article explores the system of values of the modern manager in the context of social processes, social structure, and the sociology of management. The authors set the task to determine the degree of importance of such “parameters” as gender, age, the length of management activity, etc. in management systems and processes, paying particular attention to the professional priorities and values that contribute to success in business.Methodology and sources. Based on quantitative and qualitative studies of the works of various authors the management mechanism in the context of modern science is analyzed and the relationship between personality and management style is established through values and the system of values of the person – the theoretical basis of the study. The empirical basis of the study consisted in the data obtained during an in-depth interview in which active managers of different age, length of employment and employment status were interviewed to form an idea of the manager's activity in modern Russian organizations and to determine their professional priorities and values influencing their success.Results and discussion. As a result of the study, it was found that, since the formation of the manager values is influenced by various social factors and peculiarities of individual development, it is necessary to consider the management activity in the light of sociology. The range of values significant for the manager, personal and those for achieving success in business, is as follows: family, health, systems thinking, implementation of ideas and constant self-development.Conclusion. The authors conclude that the basis for the modern manager success is not only a good state of internal talent, including with similar values but also his ability to be responsive to all changes and be ready to clearly reorganize and adapt the parts of his business. The inclusion of the systems thinking as a priority value in his management function structure will give an additional advantage in this regard.